(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
Between the half of 60s and 70s, Ludovico Quaroni is in Apulia to carry out a series of projects, including the drafting of the town-planning scheme of Bari. Thanks to his being very often in Bari and thanks to his new project, that for the first time tried out an approach to the city according to his vision of "city-territory", vision which is alternate to the current so-called "new dimension", in 1973 two entrepreneurs of the Capitanata (Nicola and Giuseppe Daloiso brothers) sent for the roman master to project a residential settlement in the neighborhood of Margherita di Savoia.